Identification of raloxifene as a novel α-glucosidase inhibitor using a systematic drug repurposing approach in combination with cross molecular docking-based virtual screening and experimental verification. (January 2022) - Wu, Jiaofeng; Hu, Baichun; Lu, Shuaizhong; Duan, Rong; Deng, Haoran; Li, Lele; He, Lijuan; Zhao, Yunli; Wang, Jian; Yu, Zhiguo
Abstract: α-Glucosidase is a promising target for the treatment of diabetes. Drug repurposing can increase the chances of discovering an active inhibitor. Therefore, this study aimed to identify potential α-glucosidase inhibitor using drug repurposing and in silico strategies. We identified critical amino acid residues of the three α-glucosidase proteins. Based on cross molecular docking studies of three α-glucosidase proteins and drugs in the FDA database, we screened hits with the favorable binding affinities and modes targeting the three proteins. Subsequently, an in vitro activity assay showed that raloxifene was an excellent inhibitor of α-glucosidase. Moreover, molecular dynamics simulations of raloxifene and three proteins were performed to assess the stability of the protein-hit systems in physiological conditions and clarify protein-hit interactions. We also performed the binding free energy calculation, Hirshfeld surface and alanine scanning mutagenesis analyses. These results demonstrated that binding between raloxifene and the three proteins was stable, and the critical amino acid residues of the three proteins formed stable contacts with raloxifene. The molecular mechanisms agree well with its activity, reinforcing that raloxifene is a candidate α-glucosidase inhibitor. Our study smoothes the path for the development of novel a-glucosidase inhibitors with high efficacy and low toxicity for the treatment of diabetes. Graphical abstract: Image 1 Highlights: The cross molecular docking-based virtual screening was performed to find novel α-glucosidase inhibitor from existing drugs. In vitro activity assay showed that raloxifene was an excellent inhibitor of α-glucosidase. The molecular mechanism was clarified by molecular dynamics simulations between raloxifene and three α-glucosidase proteins. The ideal performance of raloxifene with α-glucosidases was consistent with its inhibitory activity.